1998
DOI: 10.1136/ard.57.3.146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patient education on compliance with basic treatment regimens and health in recent onset active rheumatoid arthritis

Abstract: Objectives-To determine the eVects of patient education on compliance and on health in patients with active, recent onset rheumatoid arthritis (RA). Methods-A randomised, controlled, assessor blinded, one year trial. The experimental group followed an education programme. All patients started on sulphasalazine therapy. Compliance with sulphasalazine was measured by pill counting. Compliance rates with regimens of physical exercise, endurance activities, and energy conservation were measured by questionnaires. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 35 publications
7
99
1
4
Order By: Relevance
“…Brus et al 23 evaluated an intervention involving patient education meetings focusing on compliance both with medication therapy and with a number of physical activities in patients with rheumatoid arthritis. The program was implemented in groups and partners were invited to attend the meetings.…”
Section: Chronic Medical Conditionsmentioning
confidence: 99%
“…Brus et al 23 evaluated an intervention involving patient education meetings focusing on compliance both with medication therapy and with a number of physical activities in patients with rheumatoid arthritis. The program was implemented in groups and partners were invited to attend the meetings.…”
Section: Chronic Medical Conditionsmentioning
confidence: 99%
“…Bearne et al 29 Control group of healthy subjects Bell et al 30 Details of intervention not given Brighton et al 31 Non-dynamic hand exercises only Brus et al 32 …”
Section: Discussionmentioning
confidence: 99%
“…Although education about medication and medication use, as well as self-management Review interventions, are often part of the treatment in RA, adherence is seldom reported as an outcome measure in studies into the effect of these interventions [73]. Only three studies assessed the effect of a medication adherence intervention in RA using adherence as an outcome measure [74][75][76]. One study demonstrated an improvement in adherence to d-penicillamine following a patient education program, including seven one-to-one visits of 30 min each [14].…”
Section: Interventions In Ramentioning
confidence: 99%